2013
DOI: 10.1016/j.jacc.2013.04.036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integration of a Multidetector Computed Tomography Annulus Area Sizing Algorithm on Outcomes of Transcatheter Aortic Valve Replacement

Abstract: The implementation of an MDCT annulus area sizing algorithm for TAVR reduces PAR. Three-dimensional aortic annular assessment and annular area sizing should be considered for TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
2
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 321 publications
(164 citation statements)
references
References 21 publications
4
152
2
6
Order By: Relevance
“…MDCT is widely used for the evaluation of the annulus before TAVR and is deemed the most reliable and reproducible method of annular evaluation. [7][8][9] The results of the present study demonstrated that the aortic annulus after AVNeo is similar to that of a normal aortic valve. The AVNeo group had lower peak pressure gradients than the AVR group, as demonstrated by postoperative UCG.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…MDCT is widely used for the evaluation of the annulus before TAVR and is deemed the most reliable and reproducible method of annular evaluation. [7][8][9] The results of the present study demonstrated that the aortic annulus after AVNeo is similar to that of a normal aortic valve. The AVNeo group had lower peak pressure gradients than the AVR group, as demonstrated by postoperative UCG.…”
Section: Discussionsupporting
confidence: 68%
“…Further, reproducible annulus measurements play an increasingly important role in pre-TAVR evaluations. [7][8][9] The aim of the present study was to use MDCT to evaluate changes to the aortic annulus during the cardiac cycle after AVNeo.…”
Section: Introductionmentioning
confidence: 99%
“…The stent frame houses a trileaflet bovine pericardial valve and is surrounded in its inflow half by the Adaptive Seal TM thus mitigating PVR. The valve is available in three sizes (23,25, and 27 mm) covering aortic annuli from 19 to 27 mm. In contrast to the other devices it is mechanically expanded and locked in its final configuration by connecting the buckles to the posts.…”
Section: Boston Lotusmentioning
confidence: 99%
“…However, the new generation Evolut-R TM presents several improvements namely:) the inflow portion is wider and more cylindrical providing a flatter landing zone to ensure maximum over-sizing within the full target implant depth range, (iii) the geometry of the distal diamond cell of the inflow portion has been modified with a slightly asymmetric configuration and extended length for better conformability and consistent radial force across a range of annulus sizes, (iv) the distal skirt has been extended with a scalloped design creating a longer landing zone for better sealing, (v) the prosthesis is fully repositionable and retrievable before final detachment of the hooks (up to three times) and, (vi) the 14 Fr profile of the delivery system (true outer diameter 18 Fr), with the option of proceeding to sheath-less procedures reduces the rate of vascular complications. At the moment the device is available in three sizes (23,26, and 29 mm) covering aortic annuli from 18 to 26 mm. In addition, whereas positioning of the actual MCV can be sometimes challenging, the 1:1 ratio applied to the handle and prosthesis unsheathing-resheathing response aims at achieving more controlled and accurate positioning even in difficult anatomies [3].…”
mentioning
confidence: 99%
“…8 Over the last decade multidetector computed tomography (MDCT) has asserted itself as an important tool for the assessment of patients prior to TAVR and has been shown to help improve clinical outcomes. 9,10,11 Pre-procedural screening with 3-dimensional MDCT has resulted in a reduction in paravalvular regurgitation and also a more comprehensive evaluation of coronary obstruction risk. The clinical role of MDCT in the advance of transcatheter ViV therapy is less well established.…”
Section: Introductionmentioning
confidence: 99%